2013
DOI: 10.1111/grs.12013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moisture control, addition of glucose, inoculation of lactic acid bacteria and crushing process on the fermentation quality of rice grain silage

Abstract: To identify the best ensiling process and moisture content for rice grain silage, we determined the effects of additive (i.e. no additive, glucose additive or lactic acid bacteria [LAB] inoculation), crushing process (non‐crushing or crushing) and moisture control (none [13.6%], 20.0, 27.5, 35.0, 42.5 or 50.0% moisture content [in fresh matter, FM]) on rough rice and brown rice. Forage rice harvested at the fully ripe stage was ensiled in small‐scale experiments, and the silage was stored for 60 days. Regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In our previous study with pouch silos, rice grain silage with no additives resulted in ethanol production (Inoue et al . ). However, in the same study, we found that inoculation with LAB combined with the crushing process and adjustment of FM moisture content above 27.5% reduced ethanol production and enhanced lactic acid fermentation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In our previous study with pouch silos, rice grain silage with no additives resulted in ethanol production (Inoue et al . ). However, in the same study, we found that inoculation with LAB combined with the crushing process and adjustment of FM moisture content above 27.5% reduced ethanol production and enhanced lactic acid fermentation.…”
Section: Discussionmentioning
confidence: 97%
“…This confirms at the farm scale the results of our previous laboratory study, which suggested that the optimal pretreatment for ensiling rice grain is crushing, LAB inoculation and adjusting the moisture content of FM to about 30% (Inoue et al . ). After 1 year of storage, the lactic acid content had decreased, but the pH was stable at the desired level.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations